Retroperitoneal Laparoscopic Surgery for Retrocaval Ureter: A case Series (KYAMC Journal, 2019)
Background: Retrocaval ureter also referred to as circumcaval ureter or preureteral venacava is a rare congenital anomaly with the ureters passing posterior to the inferior vena cava (IVC). The ureter classically course medially behind the inferior venacava winding around it and then passes laterally in front of it to then course distally to the bladder. Though it is a congenital anomaly, patients do not normally present with symptoms until the 3rd and 4th decades of life from a resulting hydronephrosis. This hydronephrosis may be due to kinking of the ureter. The ureteric segment is a dynamic or compression against the psoas muscle. It was initially considered as aberration in ureteric development; however current studies in embryology have led to it being considered as an aberration in the development of the inferior vena cava.Objectives: The aim of our study was to explore the safety, feasibility and usefulness of retroperitoneoscopic surgery for retrocaval ureter performed in a single centre and to assess the short-term outcomes of patients treated with this surgical approach.Materials and methods: Eight patients underwent retroperitoneoscopic transposition of ureter between March 2014 and November 2016, A 3-port, ballon-dissecting, retroperitoneal approach was used, no open conversion was required. Follow-up studies were performed with intravenous urography and ultrasonography.Results: Mean operating time was 121 minutes (range 92-178) and mean anastomotic time was 56 minutes for all cases. Blood loss was minimum. None of the patients required blood transfusion. No intraoperative complications occurred. Hydronephrosis in all patients were decreased substantially after surgery.Conclusion: Our results have demonstrated that retroperitoneoscopic transposition of ureter is an excellent minimally invasive treatment option for a retrocaval ureter that can be accomplished quickly and safely.KYAMC Journal Vol. 9, No.-4, January 2019, Page 173-176